Analisis Perbandingan Kinerja Keuangan menggunakan Altman Z-score Sebelum Dan Saat Pandemi Covid-19 - Iis Alisa Sarif (Journal AGENCY, 2023)
This research aims to determine financial performance using Altman Z-score analysis before and during COVID-19 in the Mining sector listed on the IDX. The data used in this study is financial data derived from the annual reports of 47 mining sub-sector companies on the Indonesia Stock Exchange from 2017 to 2022. The analytical tool used is the Wilcoxon Rank Test different test using SPSS 23. The results showed that the assessment of financial performance using the Altman Z-score before the pandemic in 2017-2019 showed a figure of 3,609 or on average Mining companies did not experience bankruptcy. Meanwhile, from 2020 to 2022, during the COVID-19 pandemic, the figure was 2,408 or in the category of being prone to bankruptcy (gray area). Statistically, the change in financial performance was significant with the direction of change, namely a decline in 2020-2022 or during the Covid-19 pandemic.